Modelagem para a análise de desempenho de eletrodomésticos à força-motriz diante de distúrbios de qualidade da energia - Bacca, Ivandro Antonio (2008)
Nowadays, the problems related to Power Quality have motivated great efforts from researchers worldwide. Among the areas of interest, emerge the researchs associated to the operation of electro-electronic devices, wich are frequently found in industrial, commercial and residential installations. Considering the performance analysis, the sensibility and supportability of such equipments have become a matter of major concern in this context. These issues is quite relevant specially when considering the equipment dependence with the supply conditions as well as consumers refunding problem related to damaged equipments. Recognizing the importance of such matter, this work goes towards the investigation of the relationship between the power quality and the performance of equipments of the so called White Line : refrigerators, freezers, air conditioners, washing machines and dishwashers.